STRATEGI BANK BNI SYARIAH KCP KOLAKA DALAM MENINGKATKAN MARKET SHARE MENURUT PERSPEKTIF ISLAM - Fatmawati Fatmawati; Muhammad Ridwansyah; Muh Yusuf (Jurnal Ekonomi Bisnis Syariah, 2020)
This study aims to determine how the strategy of Bank Bni Syariah Kcp Kolaka in increasing its market share and how to review market share in an Islamic perspective. This research was conducted from November to December 2020. The object of this research is the leadership of the Bank Bni Syariah Kcp Kolaka and some. customers who transact at Bank Bni Syariah Kcp Kolaka. The research method used is qualitative research, namely the specific linkage to the study of social relations related to the facts of the pluralization of the world of life. This method is applied to see and understand the subject and object of research which includes people, institutions based on facts that appear as they are. Through this approach, a picture of the actualization, social reality, and perceptions of research objectives will be revealed. The data collection method used was direct interviews with the leadership of Bank BNI Syariah Kcp Kolaka, direct observation of certain objects that became the focus of research to find out how the bank's strategy in increase its market share and take documentation related to this research. The strategy of Bank Bni Syariah Kcp Kolaka in increasing market share, using the strategy of Door to door, Advertising, Pick up balls, People (people), Process (process), Cuestumer service. Bank BNI Syriah KCP Kolaka uses 9 Islamic marketing concepts, namely fairness, willingness to be equally willing and the right to khiyar (the right to cancel transactions), not cheating, effort, trust / responsibility, fairness, transparency / openness, honesty, sincerity / sincerity.